Utilization of Pseudomonas fluorescens Bacteria in Weed Control and Phosphate Supply in Oil Palm (Elais Guineensis Jacq.) Plantations - Revitaningrum, Aliyah; Lay, Audrey Josephine; Iskandar, Kania Ramadhani; Razhin, Muhammad Nabil (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2024)
With growing environmental concerns, sustainable management practices in oil palm plantations are becoming increasingly essential. This review examines the potential of Pseudomonas fluorescens as a biological agent for both weed control and phosphate solubilization in oil palm (Elaeis guineensis) cultivation. A systematic literature search was conducted across Google Scholar, Scopus, and ScienceDirect databases, focusing on studies published between 2007 and 2023. Studies that investigated the role of Pseudomonas fluorescens in enhancing plant growth through weed suppression or improving phosphate uptake were selected. The findings reveal that Pseudomonas fluorescens can significantly benefit plant health by minimizing weed competition and enhancing the availability of phosphorus in the soil. However, challenges such as the variability in environmental conditions, strain specificity, and scalability of application persist. The review highlights the importance of further field trials and experimental research to refine the practical use of Pseudomonas fluorescens in achieving more sustainable oil palm production.